Some comments related to the international child abduction as regulated by the Council Regulation (EU) no. 1111/2019 and the Romanian Case Law - Anițe, Nadia-Cerasela; Mareș, Cristian (CUADERNOS DE DERECHO TRANSNACIONAL, 2022)
Considering that the international child abduction has increased nowadays, as it results from the Romanian case law, we have decided to study this part of the new Council Regulation (EU) 2019/1111 of 25 June 2019 on jurisdiction, the recognition and enforcement of decisions in matrimonial matters and the matters of parental responsibility, and on international child abduction (hereinafter referred to as the “Regulation No. 1111/2019”). For this purpose, we shall also outline the differences between the Regulation No. 1111/2019 and the Council Regulation (EC) No. 2201/2003 of 27 November 2003 concerning jurisdiction and the recognition and enforcement of judgments in matrimonial matters and the matters of parental responsibility, repealing Regulation (EC) No 1347/2000 (hereinafter referred to as the “Regulation No. 2201/2003”), which shall be repealed by the Regulation No. 1111/2019 from the 1st of August 2022. The international child abduction is included in the title of a regulation for the first time. As well, a special chapter related to the international child abduction was inserted – Chapter III, articles 22-29. This amendment included by the Regulation No. 1111/2019 is not only useful, but also natural, given that the issue of the international child abduction is a complete separate issue from the parental responsibility and the exercise of this responsibility. The new Regulation No. 1111/2019 provides clarifications in relation to the period when the seised court must give its decision, in article 24, entitled Expeditious court proceedings. In accordance with the legal provisions of both the Regulation No. 1111/2019 and the 1980 Hague Convention, for ordering the return of a child the following conditions must be met: (i) there has been a breach of the rights of custody, (ii) the person, institution or other body having the care of the person of the child was actually exercising the custody rights at the time of removal or retention, (iii) the child was habitually resident immediately before the wrongful removal or retention in the state where the return is requested, (iv) the person, institution or other body having the care of the person of the child had not consented to or subsequently acquiesced in the removal or retention, (v) no exception provided by articles 12 and 13 of the 1980 Hague Convention applies.